Estudo sobre a dinâmica sazonal da pesca da albacora branca no Atlântico Sul (décadas de 1970 a 2000) - CONCEIÇÂO, Eloise Campos da (2019)
Tuna and Billfishes include the most economically important species of the fish trade. All are Oceanic and capable of long migrations or movements. The albacore tuna is one of which heats the fishing trade in general, for canning, to obtain the best prices, due to its white meat, since it is one of the most economically important and one of the most abundant fisheries resources in the South Atlantic Ocean. In order to contribute to the better known the profile of this fish fishery in the South Atlantic stock operated by the Brazilian fleet, taking into consideration the complexity of their fishery and its importance, this work presents a synthetic assessment of the evolution of fishing albacore longliners in the South Atlantic Ocean, between the 1970s and 2000s, representing the distribution of effort that targets the capture of fish, their capture and characterize bycatch from data provided by ICCAT (International Commission of the Conservation of Atlantic Tuna).The maximum fishing efforts were historically performed in compliance with the seasonal migration patterns of foraging and reproduction of fish, the fleet which contributed to his capture was historically Taiwan, even intended, in the 1990s, part of their boats catching bigeye tuna fishing as an alternative, which was also the chief representative of the bycatch, with 61 % of the total catch. Given the behavior of fishing fleets strategist, revealing dynamics efficient response to market demands, seeking to promote efficiency in the capture of the species most economically important and required, the declining CPUE of albacore white and display the same homogeneity in this study, relatively independent of stress concentration, seem more tied to these strategies such as fishing with a possible state of over-fishing of the species. Consequently, it could lead to an underestimation of CPUE of fish, due to an over-evaluation of non-target effort. Although ICCAT have concluded that this stock is probably over-exploited, also suggests the successful recovery is maintained even their current catch, which are below the tolerable total, the commission allowed by ICCAT.